2001
DOI: 10.1021/ma002039u
|View full text |Cite
|
Sign up to set email alerts
|

Chain Orientation and Its Effect on Mobility at a Rubbed Surface

Abstract: We have measured the tracer diffusion coefficient in PS films oriented by surface rubbing. The results show that the diffusion perpendicular to the rubbed surface is slower in oriented than in nonoriented chains. The decrease of the diffusion coefficient was correlated with the total oriented volume as determined by birefringence measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Fluorescence recovery after photo-bleaching performed on thin PS films, which probes the in-plane diffusion, has shown that the diffusion coefficient of a dye increases (by up to two orders of magnitude) as the film thickness decreases [63,64]. The alignment of polymer chains by rubbing has also been shown to decrease the diffusion of short chains out of the surface layer (i.e., the diffusion perpendicular to the surfaces decreases) but only by a factor 2 [65]. Our drying experiments, and the absorption experiments of Vogt et al [23,25], only probe the diffusion perpendicular to the film surfaces.…”
Section: Time Dependencementioning
confidence: 99%
“…Fluorescence recovery after photo-bleaching performed on thin PS films, which probes the in-plane diffusion, has shown that the diffusion coefficient of a dye increases (by up to two orders of magnitude) as the film thickness decreases [63,64]. The alignment of polymer chains by rubbing has also been shown to decrease the diffusion of short chains out of the surface layer (i.e., the diffusion perpendicular to the surfaces decreases) but only by a factor 2 [65]. Our drying experiments, and the absorption experiments of Vogt et al [23,25], only probe the diffusion perpendicular to the film surfaces.…”
Section: Time Dependencementioning
confidence: 99%
“…[31][32][33][34] In some cases, the surface chain conformations deviate from those of the equilibrium state lms, and the surface chains may exhibit various aggregative structures, which may result in a deviation of chain dynamics from those of the equilibrated "melt-like" surface chains. [35][36][37][38][39][40] Reports have shown that the molecular aggregative state effects can dominate the surface dynamics. [35][36][37][38][39][40] The diffusion rate of highly oriented surface chains perpendicular to the chain alignment direction is slower than that of the non-oriented chains.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases the surface chain conformations deviate from those of equilibrium state lms and the surface chains may exhibit various aggregative structures, which may result in a deviation of the chain dynamics from those of the equilibrated "melt-like" surface chains. [15][16][17][18][19][20] Some reports have shown that the molecular aggregative state effects can dominate surface dynamics. [15][16][17][18][19][20] It has been reported that for highly oriented surface chains, their diffusion rate perpendicular to the chain alignment direction is slower than that of the nonoriented chains.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Some reports have shown that the molecular aggregative state effects can dominate surface dynamics. [15][16][17][18][19][20] It has been reported that for highly oriented surface chains, their diffusion rate perpendicular to the chain alignment direction is slower than that of the nonoriented chains. 16,17 Briggs et al 18 found that a spherical selfentangled PS single chain on a lm surface has a T g lower than that of the equilibrated "melt-like" PS chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation